Exploring the strategies that midwives in British Columbia use to promote normal birth - Michelle M. Butler (BMC, 2017)
Abstract Background Rates of normal birth have been declining steadily over the past 20 years, despite the evidence of the benefits to mother and baby. This is most obvious in steadily increasing caesarean section rates across countries and studies of the factors involved suggest it may be more to do with the organization of maternity care and the preferences of healthcare providers than changes in maternal or demographic conditions. The proportion of women in British Columbia (BC) receiving care from a midwife continues to grow and there is a particular focus on promoting and supporting normal pregnancy and birth in the midwifery philosophy of care. In BC, women receiving care from a midwife are less likely to have a caesarean section and other birth interventions. Methods An interpretive approach, based on interpretive phenomenology was used to explore the experiences of midwives in BC of normal birth and the strategies that they use to keep birth normal. Fourteen experienced midwives were purposively selected from across the range of practice, geographical, and rural/urban contexts to participate in depth interviews. Data were analyzed using Thematic Network Analysis. Results Seven key themes were identified in the data: working with women from the early pregnancy, informing choice, the birth environment, careful watching and waiting, managing early labour, helping the woman to cope with labour, and tools in the tool kit. Conclusions Midwives in BC work closely with women from early pregnancy to prepare them for a normal birth, and as "instruments of care" they adopt a range of approaches to support women to achieve this. The emphasis on continuity of care in the BC model of midwifery care plays a vital role in this.